Contamination of a drug consumption room with drugs and potential risks for social health care workers - Flore Cuffaro; Georges Dahm; Claude Marson; Patrick Berlemont; Michel Yegles; Claudia Allar; Lionel Fauchet; Matteo Creta; Serge Schneider (BMC, 2024)
Abstract Background Studies have shown that contamination of surfaces by illicit drugs frequently occurs in forensic laboratories when manipulating seized samples as well as in pharmacies and hospitals when preparing medicinal drugs. In this project, we extended these studies to a Drug Consumption Room to investigate drug levels and possible exposure of the staff members. Methods We investigated pre and post cleaning contamination by heroin and cocaine and their degradation products 6-monoacetylmorphine and benzoylecgonine on different surfaces (tables, counters, computers and door handles) and in the ambient air. We also collected urine and hair samples from staff members to check for potential short and long term contaminations. Results Medium to heavy contamination has been detected on most surfaces and door handles; as expected, air contamination was particularly high in the smoking room. Drug levels were < LOD to very low in the urine and the hair samples of staff members tested. Conclusion The cleaning efficiency of the surfaces, carried out by staff and drug users after drug consumption, was often not satisfactory. The very low drug levels in hair indicate that acute health risks for staff members are low.